Systematic Review of Global Research on Acculturation of International Students (2003-2023) - Zhao, Zhao; Bava Harji, Madhubala (Journal of International Students, 2024)
Aim: This paper presents a scientometric review of global articles regarding acculturation of international students (AoIS), published from 2003 to 2023 and indexed in the Web of Science Core Collection (WoSCC), to provide a quantifiable snapshot of the field. Methodology: Bibliographic information was extracted from WoSCC. Refined data were visualized using CiteSpace. Conclusion: Worldwide publications have been increasing continuously since 2013, with a staged development among relevant disciplines. Limited collaborations have been found among countries, institutions, and posting authors, however a gradual trend toward transnational teamwork has been emerging. Research foci mainly concentrate on macro factors of acculturation. Research gaps have also been revealed, as hotspots in recent pedagogical research field have not been adopted in studies of AoIS.